Women on Board and Its Impact on Financial Performance: Evidence from Capital Goods Companies in Sri Lanka - Sangeerana, C.; Kengatharan, L.; Jeyan Suganya, D.F.; Mithila, G. (University of Vavuniya, 2022)
This study focuses on gender diversity and investigates to what extent women on the board influence the financial performance of the capital goods companies listed in CSE. The Independent variable of the study is women on board, while the dependent variable is the company's financial performance. Hence this study considers board diversity, women executive directors and independent non-executive directors to measure women on board and, at the same time to measure the company's financial performance, return on equity and return on assets are considered. The control variables are leverage and firm size. Secondary data from 2015 to 2020 were collected from the annual report of 20 companies. Traditionally accepted methods, namely descriptive statistics, unit root test, correlation analysis and regression analysis, were employed for descriptive research designs. The study reveals that board diversity, women independent non executive directors and leverage have a significant negative impact on ROA while board diversity has a significant negative impact on ROE. Furthermore, it proves that Sri Lankan women are typically still engaging more with family responsibilities than men. Thus, they usually don’t care about being involved in the corporate ladder and representing themselves on board the company. Therefore, this study recommends providing sufficient training through seminars, workshops, forums, and on-the-job training to enhance women's knowledge and leadership skills for making decisions to enhance the firm's financial performance.
Keywords: Board Diversity; Corporate Governance; Financial Performance; Women on Board